Controllable Construction of Core–Shell Polymer@Zeolitic Imidazolate Frameworks Fiber Derived Heteroatom‐Doped Carbon Nanofiber Network for Efficient Oxygen Electrocatalysis. Issue 19 (26th March 2018) - Zhao, Yingxuan; Lai, Qingxue; Zhu, Junjie; Zhong, Jia; Tang, Zeming; Luo, Yan; Liang, Yanyu
Abstract: Designing rational nanostructures of metal–organic frameworks based carbon materials to promote the bifunctional catalytic activity of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is highly desired but still remains a great challenge. Herein, an in situ growth method to achieve 1D structure‐controllable zeolitic imidazolate frameworks (ZIFs)/polyacrylonitrile (PAN) core/shell fiber (PAN@ZIFs) is developed. Subsequent pyrolysis of this precursor can obtain a heteroatom‐doped carbon nanofiber network as an efficient bifunctional oxygen electrocatalyst. The electrocatalytic performance of derived carbon nanofiber is dominated by the structures of PAN@ZIFs fiber, which is facilely regulated by efficiently controlling the nucleation and growth process of ZIFs on the surface of polymer fiber as well as optimizing the components of ZIFs. Benefiting from the core–shell structures with appropriate dopants and porosity, as‐prepared catalysts show brilliant bifunctional ORR/OER catalytic activity and durability. Finally, the rechargeable Zn‐air battery assembled from the optimized catalyst (CNF@Zn/CoNC) displays a peak power density of 140.1 mW cm −2, energy density of 878.9 Wh kgZn −1, and excellent cyclic stability over 150 h, giving a promising performance in realistic application. Abstract : An in situ growth and carbonization strategy to synthesize heteroatom‐doped carbon nanofiber network for efficient oxygen electrocatalysis is reported. The growth process and components of ZIFs regulated on polymer fiber could generate a porous carbon nanofiber with highly active sites density, which shows brilliant bifunctional oxygen reduction reaction/oxygen evolution reaction catalytic activity and high performance in a Zn‐air battery.